A Finite Element Model for Investigating Unsteady-State Temperature Distribution and Thermomechanical Behavior of Underground Energy Piles - Peng Zhao; Xiaozhao Li; Lihua Hu; Yun Wu; Chenyang Zhang (Applied Sciences, 2022)
The underground energy geostructure represented by the energy pile is one of the key paths for the cooperative development of underground space and geothermal energy. Because of its advantages of low cost, high efficiency and no extra occupation of underground space, it has become a feasible alternative to the borehole heat exchanger. The change in the temperature field of the energy pile and its surrounding ground not only affects the geological environment but also influences the thermomechanical performance and the durability of the structure. However, the temporal and spatial unsteady-state temperature distribution of piles and surrounding rock under typical intermittent and unbalanced thermal load conditions is still unclear. In this paper, a finite element model was applied to analyze the unsteady-state temperature distribution, and the thermomechanical behavior of the energy pile group was developed and verified. The temperature field distribution of pile and surrounding rock under typical intermittent working and unbalanced thermal load conditions were determined. Moreover, the thermomechanical behavior characteristics of the energy pile group were investigated. Finally, the influences of pile layout on the thermomechanical behavior of the energy pile group were identified by designing six different scenarios. The results indicate that under typical intermittent operation conditions, the temperature of the energy pile and surrounding ground near the heat exchange pipe varies periodically. For areas with unbalanced cooling and heating loads, long-term operation of energy piles leads to thermal accumulation, and the maximum temperature of energy piles occurs in the first daily cycle. In summer/winter working conditions, the increase/decrease in pile temperature induces axial compression/tensile stress. When the pile group is partially used as the energy pile, the non-energy pile acts as the “anchor pile”, and it generates the added tensile stress.